03 PROSPEK PENGEMBANGAN USAHATANI UBI JALAR DI DESA LIMAPOCCOE KECAMATAN CENRANA KABUPATEN MAROS - Jurnal Agribis; Nesmawati Nesmawati; Zulkifli Zulkifli; Mohammad Anwar Sadat (Jurnal Agribis, 2020)
Sweet potato is a plant food source of vegetable protein that is widely cultivated both on sweet potato agribusiness land in this area has the prospect to be developed considering the available land resources are quite extensive, climatic conditions are suitable, sweet potato cultivation technology is quite available, human resources are quite skilled. In farming and the market is still wide open for sweet potato commodities. This research was conducted in Cenrana Subdistrict, Maros Regency. This location was chosen because most of the people in this village are sweet potato producers. There are two data used, namely: primary data, namely data obtained directly from the results of observations through direct interviews and also through the help of questionnaires, and secondary data, namely data obtained from agencies / institutions related to and related to this research. The purpose of this study was to determine the prospects for the development of sweet potato farming and to determine the yield of the farmers in Cenrana District. Data is collected from survey results using questionnaires plus field observations. The data that has been collected is then tabulated to obtain real data used for analysis purposes. This study used the SWOT analysis method to determine the prospects for the development of Sweet Potato Farming in Cenrana District, Maros Regency, the production of sweet potato farmers. The results showed that the prospect of sweet potato farming was in quadrant 1 (one). This quadrant describes a very favorable situation for developing this farm.